A study on neutrosophic soft set and neutrosophic hypersoft set - Hema Rengaswamy; Rajeshwari Subramani; Florentin Smarandache (Journal of Fuzzy Extension and Applications)
This paper mainly intends to verify whether the basic laws of set theory apply in the Neutrosophic Soft Set (NSS). The laws examined in this paper for NSS include Commutative law, Associative law, Distributive law, Involution law, Idempotent law, and Negation law (law of contradiction and law of excluded middle). It has also been illustrated with sufficient examples. In addition, extending that to the hypersoft set, we have proved if H is a Neutrosophic hypersoft Subgroup (NHSSG) of a group G and N is a normal subgroup of G, then HN is a NHSSG of G.